Three-Year Follow-Up of protection Rates in Children Given Varicella Vaccine - David W Scheifele; Scott A Halperin; Francisco Diaz-Mitoma (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the rate and severity of subsequent varicella and zoster among children given a varicella vaccine.